Acid-adapted cancer cells alkalinize their cytoplasm by degrading the acid-loading membrane transporter Anion Exchanger 2 (SLC4A2) - Michl, J; Monterisi, S; White, B; Blaszczak, W; Hulikova, A; Abdullayeva, G; Bridges, E; Yin, Z; Bodmer, W; Swietach, P (Cell Press, 2023)
Acidic environments reduce the intracellular pH (pHi) of most cells to levels that are sub-optimal for growth and cellular functions. Yet, cancers maintain an alkaline cytoplasm despite low extracellular pH (pHe). Raised pHi is thought to be beneficial for tumor progression and invasiveness. However, the transport mechanisms underpinning this adaptation have not been studied systematically. Here, we characterize the pHe-pHi relationships in 66 colorectal cancer cell lines and identify the acid-loading Anion Exchanger 2 (AE2, SLC4A2) as a regulator of resting pHi. Cells adapt to chronic extracellular acidosis by degrading AE2 protein, which raises pHi and reduces acid-sensitivity of growth. Acidity inhibits mTOR signaling, which stimulates lysosomal function and AE2 degradation, a process reversed by bafilomycin A1. We identify AE2 degradation as a mechanism for maintaining a conducive pHi in tumors. As an adaptive mechanism, inhibiting lysosomal degradation of AE2 is a potential therapeutic target.